Cognitive interviewing methodology - Miller, Kristen (Hoboken, New Jersey : Wiley, 2014)
"Acknowledging the impact of sociological factors on the survey process, this book introduces a paradigm for the cognitive interview process. It introduces the interpretive approach to cognitive interviewing, presents the underlying theoretical foundations, and explores the issues relating it. The book also addresses the various aspects of data collection, analysis, and documentation. It is an ideal reference for survey researchers and practitioners in the social sciences who utilize these techniques in their everyday work and as a supplement for courses on survey methods at the upper-undergraduate and graduate levels"--
Machine generated contents note: Acknowledgements Contributors Foreword Gordon Willis 1. Introduction Kristen Miller 2. Foundations and New Directions Valerie Chepp and Caroline Gray 3. Data Collection Stephanie Willson and Kristen Miller 4. Analysis Kristen Miller, Stephanie Willson and Valerie Chepp 5. Assessing Translated Questions via Cognitive Interviewing Alisú Schoua-Glusberg and Ana Villar 6. Conveying Results Valerie Chepp and Paul Scanlon 7. Case Study: Evaluation of a Sexual Identity Question Kristen Miller and J. Michael Ryan 8. Analysis Software for Cognitive Interviewing Studies: Q-Notes & Q-Bank Justin Mezetin and Meredith Massey 9. Cognitive Interviewing in Mixed Research Isabel Benitez Baena and Jose-Luis Padilla 10. Conclusion Kristen Miller, Stephanie Willson, Valerie Chepp and Jose-Luis Padilla Key Concepts Question Evaluation Resources Bibliography .
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Interviewing; Cognition; Questionnaires -- Methodology; Social surveys -- Methodology; Social sciences -- Research -- Methodology; Psychology -- Research -- Methodology; MATHEMATICS / Probability & Statistics / General; SOCIAL SCIENCE / Statistics; Cognition; Interviewing; Psychology -- Research -- Methodology; Questionnaires -- Methodology; Social sciences -- Research -- Methodology; Social surveys -- Methodology; Interviewing; Cognition; Questionnaires / Methodology; Social surveys / Methodology; Social sciences / Research / Methodology; Psychology / Research / Methodology; SOCIAL SCIENCE / Statistics; Electronic books; Electronic books